Green tea–induced epigenetic reactivation of tissue inhibitor of matrix metalloproteinase‐3 suppresses prostate cancer progression through histone‐modifying enzymes. Issue 7 (10th March 2019) - Deb, Gauri; Shankar, Eswar; Thakur, Vijay S.; Ponsky, Lee E.; Bodner, Donald R.; Fu, Pingfu; Gupta, Sanjay
Abstract: Green tea polyphenols (GTPs) and their major constituent, epigallocatechin‐3‐gallate (EGCG), have been reported to demonstrate many interesting biological activities, including anticancer properties. Recent studies on prostate cancer provide strong evidence that epigenetic mechanisms are major players in the regulation of matrix metalloproteinases (MMPs) and their binding partner tissue inhibitor of MMPs (TIMPs) involved in prostate cancer progression. Here we demonstrate that GTP/EGCG mediate epigenetic reactivation of TIMP‐3 that plays a key role in suppressing invasiveness and cancer progression. Treatment of human prostate cancer DUPRO and LNCaP cells with 10 µg/mL GTP and 20 µM EGCG induced TIMP‐3 mRNA and protein expression. This transcriptional activation of TIMP‐3 was associated with the decrease in the expression of both enhancers of zeste homolog 2 (EZH2) and its catalytic product trimethylation of histone H3 at lysine 27 (H3K27me3) repressive marks at the TIMP‐3 promoter with an accompanying increase in histone H3K9/18 acetylation. In addition, GTP/EGCG treatment significantly reduced class I histone deacetylase (HDAC) activity/expression and EZH2 and H3K27me3 levels in prostate cancer cells. EGCG/GTP exposure also reduced MMP‐2/MMP‐9 gelatinolytic activity and abrogated invasion and migration capabilities in these cells. Silencing of EZH2 and class I HDACs strikingly increased the expression of TIMP‐3 independent of DNA methylation. Furthermore, clinical trials performed on patients undergoing prostatectomy consuming 800 mg EGCG (Polyphenon E) up to 6 weeks and grade‐matched controls demonstrate an increase in plasma TIMP‐3 levels. A marked reduction in class I HDACs activity/expression and EZH2 and H3K27me3 levels were noted in GTP‐supplemented prostate tissue. Our findings highlight that TIMP‐3 induction, as a key epigenetic event modulated by green tea in restoring the MMP:TIMP balance suppresses prostate cancer progression.